Spectacular infrastructure and its breakdown in socialist Vietnam - SCHWENKEL, CHRISTINA (American ethnologist, 2015)
No material resource and public good is more critical to sustaining urban life than water. During postwar reconstruction in Vietnam, planners showcased urban infrastructure as a spectacular socialist achievement. Water-related facilities, in particular, held the potential for emancipation and modernity. Despite East German-engineered systems, however, taps remained dry in socialist housing. Lack of water exposed existing hierarchies that undermined the goal of democratic infrastructure yet enabled new forms of solidarity and gendered social practice to take shape in response to the state's failure to meet basic needs. Infrastructural breakdown and neglect thus catalyzed a collective ethos of maintenance and repair as the state shifted responsibility for upkeep to disenchanted tenants. I track these processes in a housing complex in Vinh City, where water signified both the promises of state care and a condition of its systemic neglect.